Hyperlipidaemic state and cardiovascular risk in primary biliary cirrhosis. Issue 2 (1st August 2002) - Longo, M; Crosignani, A; Battezzati, P M; Squarcia Giussani, C; Invernizzi, P; Zuin, M; Podda, M
Abstract : Background: Primary biliary cirrhosis (PBC), a chronic cholestatic liver disease, is frequently associated with severe hypercholesterolaemia but the clinical significance of this finding is unclear. Aims: To characterise changes in serum lipid profile over time and to assess the risk of cardiovascular disease in PBC. Subjects and methods: We studied a cohort of 400 PBC patients for 6.2 years (range 4 months to 24 years) by serial determinations of serum lipid levels and registration of all cardiovascular events. Subjects included in an Italian prospective population based study served as controls. Results: At presentation, 76% of patients had serum cholesterol levels >5.2 mmol/l. Hyperbilirubinaemic patients had higher total cholesterol and lower high density lipoprotein (HDL) cholesterol levels (p<0.001). With time, disease progression was associated with a reduction in total (p<0.001) and HDL (p<0.05) cholesterol. The incidence of cardiovascular events was similar to that of the general population (cerebrovascular events: standardised ratio 1.4; 95% confidence interval 0.5–3.7; coronary events: 2.2; 0.9–4.3). Hypertension was associated with an increased risk of cardiovascular events (3.8; 1.6–8.9). Association with moderate hypercholesterolaemia was of borderline significance (3.8; 0.9–17) whereas severe hypercholesterolaemia was not associated with increased risk (2.4, 0.5–11). Conclusions: In PBC, serum cholesterol levels markedly increase with worsening of cholestasis, and decrease in the late disease stages, despite a severe reduction in biliary secretion. Marked hypercholesterolaemia, typical of severe longstanding cholestasis, is not associated with an excess risk of cardiovascular disease while less advanced patients with moderate hypercholesterolaemia are exposed to an increased cardiovascular risk. Putative protective factors in PBC patients with severe hypercholesterolaemia should be assessed.